Outcomes of Patients in Long-Term Opioid Maintenance Treatment. (18th September 2016) - Zippel-Schultz, Bettina; Specka, Michael; Cimander, Konrad; Eschenhagen, Thomas; Gölz, Jörg; Maryschok, Markus; Nowak, Manfred; Poehlke, Thomas; Stöver, Heino; Helms, Thomas M.; Scherbaum, Norbert
ABSTRACT: Background : Despite the importance of duration of opioid maintenance treatment (OMT), only few studies have reported outcomes of long-term OMT. Objectives : To describe outcomes of long-term (> 5 years) OMT patients with respect to substance use, physical and mental health, and socioeconomic characteristics. Methods : Patients ( n = 160) were recruited from 15 OMT offices in different regions of Germany. Data were collected using a structured interview at baseline, and clinical recordings, including urine drug screenings, during 12 monhts follow-up. Results : Patients had a mean age of 44 years. During follow-up, 23% of patients showed indications of an alcohol problem. Cannabis was used by 56%, often frequently. Heroin was used by 28%, mostly infrequently. Three quarters of patients either had a non-substance related mental disorder (48.1%, most frequently affective and anxiety disorders) or somatic diagnosis (61.3%, frequently hepatitis C, HIV, or cardiovascular diseases), or both. Unemployment rate was 43.1% at baseline (27% for patients without comorbidity) and remained generally stable during follow-up. No arrests or incarcerations were recorded. During follow-up, 2.5% of patients prematurely terminated OMT, 2.5% regularly completed OMT. Conclusions : The sample as a whole was characterized by stable living conditions, high unemployment, low illicit opiate use, and a high retention rate. Continuation of OMT could enable further treatment of comorbidity and prevent resumption of a drug-dominated lifestyle. But it may well be asked how within the context of OMT further improvements can be achieved, especially with regard to further decrease of alcohol use and the treatment of depression.